2006
DOI: 10.1213/01.ane.0000226097.22384.f4
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Properties of Sevoflurane in Patients Undergoing Aortic Valve Replacement with Cardiopulmonary Bypass

Abstract: In coronary surgery patients the use of a volatile anesthetic regimen with sevoflurane was associated with a better recovery of myocardial function and less postoperative release of troponin I. In the present study we investigated whether these cardioprotective properties were also apparent in the cardiac surgical setting of aortic valve replacement (AVR) surgery for the correction of aortic stenosis. Thirty AVR surgery patients were randomly assigned to receive either target-controlled infusion of propofol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 26 publications
0
33
0
6
Order By: Relevance
“…While numerous laboratory investigations have shown that anaesthetic preconditioning is an important protective mechanism in a variety of species and tissues [1][2][3][4], the results of studies performed in humans have been more equivocal. While there are several studies reporting a beneficial effect with respect to myocardial cell damage [5][6][7], myocardial function [8,9], and improved outcome [10,11], other investigators have been unable to confirm these promising findings [12][13][14][15]. In studies where the volatile anaesthetic is given continuously (i.e.…”
mentioning
confidence: 99%
“…While numerous laboratory investigations have shown that anaesthetic preconditioning is an important protective mechanism in a variety of species and tissues [1][2][3][4], the results of studies performed in humans have been more equivocal. While there are several studies reporting a beneficial effect with respect to myocardial cell damage [5][6][7], myocardial function [8,9], and improved outcome [10,11], other investigators have been unable to confirm these promising findings [12][13][14][15]. In studies where the volatile anaesthetic is given continuously (i.e.…”
mentioning
confidence: 99%
“…Many studies (11)(12)(13)(14)(15)(16)18,19) and reviews (21)(22) have appeared in the literature suggesting a cardioprotective effect provided by volatile anesthetics in patients undergoing cardiac procedures. A recent survey (23) conducted in 64 Italian centres, encompassing a total of 34,310 patients undergoing coronary artery bypass graft surgery, showed that risk-adjusted mortality may be reduced by the use of volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of the 22 randomized controlled studies included in the meta-analysis studied low risk patients undergoing isolated procedures (mostly coronary artery bypass grafting). Studies performed on patients undergoing coronary artery bypass graft (CABG) surgery, either with cardiopulmonary bypass (CPB) (11)(12)(13) (19) showed that an anesthetic plan with sevoflurane was associated with better preservation of cardiac function and lower cardiac troponin release peak in patients undergoing aortic valve replacement for aortic stenosis. Large multicentre randomized controlled studies in high risk populations of patients are needed to evaluate the possible influence of different anesthetic regimens on patient outcomes after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Описаны отдельные попытки клинического ис пользования ишемического прекондиционирования (ИПК) [21,43,44]. Тем не менее, более целесообразным представляется использование АПК, поскольку механиз мы его во многом схожи с ИПК [19,20], но отсутствует необходимость в использовании различных адъювантных препаратов (ингаляционный анестетик используется так или иначе, при условии выбора соответствующей методи ки анестезии), а данные об эффективности достаточно до казательны [28,31,45]. В то же время, большинство из проанализированных работ обосновывают положитель ные эффекты АПК динамикой концентрации КФК МВ, тропонинов T или I, которые способны отразить повреж дение кардиомиоцитов, но никак не нарушение его функ ции и поэтому не могут быть использованы для определе ния наличия и выраженности ПДМ.…”
Section: таблица 2 основные результаты исследованияunclassified